Contact fatigue of WC-6%wtCo cemented carbides: Influence of corrosion-induced changes on emergence and evolution of damage. Issue 4 (15th February 2022) - Zheng, Y.F.; Fargas, G.; Lavigne, O.; Serra, M.; Coureaux, D.; Zhang, P.P.; Yao, Z.H.; Zhang, Q.L.; Yao, J.H.; Llanes, L.
Abstract: The effect of corrosion-induced changes on the contact fatigue response and associated damage in a medium-grained WC-6%wtCo hardmetal grade is investigated. Cyclic contact loading tests are conducted by means of Hertzian indentation techniques. Corrosion damage is introduced in a controlled way by previous immersion of specimens in a stirred acidic medium. Results reveal that corrosion significantly affects the contact fatigue behavior of the material under consideration, in terms of decreasing the effective load bearing capability of the material as well as earlier emergence and evolution of specific damage features, as compared to those discerned under monotonic loading and in a pristine hardmetal respectively. As cycle number increases, damage evolution in the corroded condition is more gradual and diffuse than for the uncorroded one. In general, it is dominated by existence of ill-defined radial cracks together with pronounced carbide grain pull-out which finally evolve into cohesive-like spallation in regions close to the periphery of indentation imprints. These findings are rationalized on the basis of phase assemblage changes linked to corrosion, particularly in terms of lessening of toughening capability and easiness of WC grain pull-out intrinsic to the loose and porous binderless WC skeleton remnant at the surface level, after exposure to the acid medium. Although some removal of carbide grains and discrete cohesive chipping is also observed in the pristine sample for very high number of cycles, such different response, as compared to monotonic loading, is linked to oxidation phenomena of the metallic binder for this reference condition.